Cool Tools for Back to School - Ekart, Donna F. (My University, 2011)
I’d like to offer you some truly awesome library and research tools that will be useful for your school-bound patrons. For students who may use a wide variety of computers in campus labs, at home, and at your library, having simple online applications that don’t require anything but a web browser and a login can make a huge difference in the ability to get work done. All of these tools are free and can be easily linked and promoted from a page on your library’s website.